2013
DOI: 10.1007/s11030-013-9452-z
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid A, a polyphenolic derivative from Salvia miltiorrhiza bunge, as a multifunctional agent for the treatment of Alzheimer’s disease

Abstract: The effects of Salvianolic acid A (Sal A) on the treatment of Alzheimer's disease (AD) were investigated. Sal A significantly inhibits amyloid beta [Formula: see text] self-aggregation and disaggregates pre-formed [Formula: see text] fibrils, reduces metal-induced [Formula: see text] aggregation through chelating metal ions, and blocks the formation of reactive oxygen species (ROS) in SH-SY5Y cells. Sal A protects cells against [Formula: see text]-induced toxicity. Furthermore, Sal A, possibly because of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…18 As shown in Table 1, the inhibition activity for CMTF increased to 87.4% at 100 μg/mL, whereas the inhibition rate for UTF was 62.0% at the same concentration. HPLC-MS/MS experiments were performed on the UTF (Figures S1−S7, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…18 As shown in Table 1, the inhibition activity for CMTF increased to 87.4% at 100 μg/mL, whereas the inhibition rate for UTF was 62.0% at the same concentration. HPLC-MS/MS experiments were performed on the UTF (Figures S1−S7, Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 86%
“…In the successive decades, the number of pharmacological and clinical studies grew rapidly proving not only cardiovascular properties but widespread activities in several pathologies. Many interesting, promising therapeutic applications of S. miltiorrhiza extracts or single constituents have now appeared in the literature and include acute ischemic stroke [8,9], AD [10][11][12], osteoporosis [13], atherosclerosis [14], fulminant hepatic failure [15], and malignant gliomas [16]. In virtue of having few side effects, S. miltiorrhiza and its single constituents have been widely and successfully used in clinics in China, Korea, Japan, and other Asian countries for the treatment of heart and cerebrovascular disease, hepatitis, hepatocirrhosis, neuroasthenic insomnia, cancer, chronic renal failure, and dysmenorrhea [1,2,4].…”
Section: Achementioning
confidence: 99%
“…Salvianolic acid A Cao and coworkers [12] proved that SalA (50-100 µM) inhibits Aβ 42 self-mediated aggregation and disaggregates Aβ 42 aging fibrils in a dose-dependent manner. Wang and coworkers [57] demonstrated that SalA protects SH-SY5Y cells against MPP + -induced cytotoxicity.…”
Section: Salvianolic Acid Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings for S. miltiorrhiza components indicate that cryptotanshinone inhibits human glioma cell proliferation (Lu et al, 2013), salvianolic acid A can be used to treat Alzheimer's disease (Cao et al, 2013), and tanshinone I and tanshinone IIA protect the liver from acute and chronic injury (Park et al, 2009). However, although more than 20 active components have been isolated from S. miltiorrhiza, the molecules with liver-protective effects are unclear.…”
Section: Introductionmentioning
confidence: 99%